Statue at Bayanzag Museum - Bernard Gagnon (Wikimedia Commons, 2023)
Notice iconographique issue de Wikimedia Commons. Titre: Statue at Bayanzag Museum. Statue of dinosaurs at Bayanzag Museum, Mongolia
Droits : Licence Creative Commons Zero, Public Domain Dedication via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures